2017
DOI: 10.1088/1748-9326/aa5aff
|View full text |Cite
|
Sign up to set email alerts
|

Different regional climatic drivers of Holocene large wildfires in boreal forests of northeastern America

Abstract: Global warming could increase climatic instability and large wildfire activity in circumboreal regions, potentially impairing both ecosystem functioning and human health. However, links between large wildfire events and climatic and/or meteorological conditions are still poorly understood, partly because few studies have covered a wide range of past climate-fire interactions. We compared palaeofire and simulated climatic data over the last 7000 years to assess causes of large wildfire events in three coniferou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 72 publications
3
15
0
Order By: Relevance
“…The fire history reconstructed from the lakes in the study was consistent with a regime that would maintain the current ecosystem structure that has persisted over the last 1,000 years (unpublished data). This is also consistent with Remy et al () findings that showed that the fire regime, the main disturbance factor prone to cause sudden vegetation changes, had not fluctuated much at the regional scale during the last 1,000 years. We therefore hypothesized for the present study that no major changes in vegetation had occurred in both watershed types (MF vs LW) during this period, and we focused only on the top 10‐ to 50‐cm lacustrine sediment sequences.…”
Section: Methodssupporting
confidence: 92%
“…The fire history reconstructed from the lakes in the study was consistent with a regime that would maintain the current ecosystem structure that has persisted over the last 1,000 years (unpublished data). This is also consistent with Remy et al () findings that showed that the fire regime, the main disturbance factor prone to cause sudden vegetation changes, had not fluctuated much at the regional scale during the last 1,000 years. We therefore hypothesized for the present study that no major changes in vegetation had occurred in both watershed types (MF vs LW) during this period, and we focused only on the top 10‐ to 50‐cm lacustrine sediment sequences.…”
Section: Methodssupporting
confidence: 92%
“…Thesusceptibilityofthepeatlandtofire may have increased due to autogenic-driven drying and the related increase in aboveground biomass. However, charcoal reconstructions from nearby sites (<20 km from Villebois peatland) also suggested higher fire frequencies during the late Holocene (Carcaillet et al 2001;Ali et al 2008) althoughadecreaseinfirefrequencyisdocumented in the boreal biome of northeastern America during this period (Ali et al 2012;Remy et al 2017).…”
Section: Influence Of Fire On Millennial Peatland Dynamicsmentioning
confidence: 97%
“…However, it has been increasingly recognized that such an assumption is invalid and that modern observations are not a good analogue for prehistoric variability (Kelly et al, 2016;Hudiburg et al, 2017). For example, fire activity over much of the Holocene was higher in terms of frequency and fire size than the current levels across broad areas of eastern Canada (Girardin et al, 2013a;Remy et al, 2017). It is likely that not accounting for such variability may introduce biases in forest productivity dynamics and levels, more specifically on soil carbon dynamics (Hudiburg et al, 2017).…”
Section: Uncertainties and Future Perspectivesmentioning
confidence: 99%